EXPERIMENTAL STUDY OF LIQUID IMMISCIBILITY IN SILICATE-CARBONATE SYSTEMS - Suk N.I. (My University, 2001)
Silicate-carbonate liquid immiscibility was experimentally studied with application to the modeling of carbonatite melt separation from foid silicate magmas. Main attention was paid to modeling silicate-carbonate liquid immiscibility and partitioning of REE, Nb, and Ta between the immiscible phases at T = 1100 and 1250°C and P = 2 kbar. A wide field of initial melt unmixing into two liquids, silicate and carbonate, was detected. At 1100°C, a correlation was observed between the partition coefficients of rare earth elements and the initial composition of the system: in alkalic silicate-carbonate systems, rare earth elements are accumulated in carbonate phases; whereas in calcic subalkaline compositions, they are redistributed into silicate liquid. The partition coefficient of rare earth elements are also temperature-dependent: an increase in temperature from 1100 to 1250°C results in the partitioning of rare earth elements into the silicate phase, while Nb and Ta are mainly concentrated in the silicate melt. The effect of phosphorus and halogens on silicate-carbonate liquid immiscibility and partitioning of ore elements between immiscible phases was investigated. It was found that the addition of a small amount of phosphorus or fluorine into the system enhanced the extraction of rare earth elements by salt melts. In contrast, chlorine shows no similar effect and retains the indifference of salt melt with respect to the extraction of ore metals.